Sex Differences in Blood–Brain Barrier Transport of Psychotropic Drugs - Dalla, Christina; Pavlidi, Pavlina; Sakelliadou, Danai-Georgia; Grammatikopoulou, Tatiana; Kokras, Nikolaos (Frontiers in Behavioral Neuroscience, 2022)
Treatment of neuropsychiatric disorders relies on the effective delivery of therapeutic molecules to the target organ, the brain. The blood–brain barrier (BBB) hinders such delivery and proteins acting as transporters actively regulate the influx and importantly the efflux of both endo- and xeno-biotics (including medicines). Neuropsychiatric disorders are also characterized by important sex differences, and accumulating evidence supports sex differences in the pharmacokinetics and pharmacodynamics of many drugs that act on the brain. In this minireview we gather preclinical and clinical findings on how sex and sex hormones can influence the activity of those BBB transporter systems and affect the brain pharmacokinetics of psychotropic medicines. It emerges that it is not well understood which psychotropics are substrates for each of the many and not well-studied brain transporters. Indeed, most evidence originates from studies performed in peripheral tissues, such as the liver and the kidneys. None withstanding, accumulated evidence supports the existence of several sex differences in expression and activity of transport proteins, and a further modulating role of gonadal hormones. It is proposed that a closer study of sex differences in the active influx and efflux of psychotropics from the brain may provide a better understanding of sex-dependent brain pharmacokinetics and pharmacodynamics of psychotropic medicines.